ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PESERTA DIDIK SMA NEGERI 2 SEMARANG MENGGUNAKAN METODE REGRESI LOGISTIK ORDINAL - Galuh Riani Putri; Yuciana Wilandari; Triastuti Wuryandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Education can be used to determine the standard quality of life. One way to get an education is studying in the schools. In Semarang, there are several schools, one of which is SMAN 2 Semarang. In order to pass the admission selection of students at SMAN 2 Semarang, students must fulfill the requirements that had specified by the school. To determine the factors that affect the acceptance of students, the author uses ordinal logistic regression method. Ordinal logistic regression method is used to model the relationship between the response variable that consists of more than two categories and there are levels in that category with several independent variables that are categories or continuous. After doing research using ordinal logistic regression method, the result is that the factors that affect the acceptance of students of SMAN 2 Semarang is Indonesian scores, English scores, Mathematics scores, Science scores, Benefit scores, Achievement scores and also Rayon with the accuracy of the classification by 89, 63%. Keywords: Education, Admission of Students, Ordinal Logistic Regression